Differences in the Extent of Use of Culture in the Classroom Between Indigenous and Non-indigenous Teachers and the Relationship to Student Reported Academic Achievement in Reading and Math - (:unkn) unknown (My University, 2014)
With the historical lack of academic achievement of American Indian/ Alaskan Native (AI/AN) students in public schooling, Indigenous communities have expressed the need to emphasize Indigenous culture in the education of AI/AN students. This study investigated if the relationship between the use of Indigenous culture and academic achievement can be validated through the use of the National Indian Education Survey database. This study examined (1) if there is a difference in the extent of AI/AN culture used in the classroom between Indigenous teachers and non-Indigenous teachers, (2) if there is a relationship between the student reported academic achievement of AI/AN students in mathematics and the extent of the use of AI/AN culture in the classroom, and (3) if there is a relationship between the student reported academic achievement of AI/AN students in reading and extent of the use of AI/AN culture in the classroom. In conducting the study, the National Indian Education Study (NIES) Part II Grade Four Student and Teacher survey questionnaire database was utilized. Ten of the NIES questionnaire items pertaining to the use of culture in the classroom were used to create a new construct; Cronbach's alpha analysis was conducted to test this scale for reliability and was found to have high reliability with a Cronbach's alpha = .877. Using the new scale construct for extent of culture use in the classroom, classroom teachers of Indigenous (AI/AN/NH/PI) background were compared to classroom teachers of non-Indigenous background to determine if there was a difference in the extent of culture used in the classroom between the two; results of the t-test, t(2357) = -22.241, p Chi-square analysis was performed to determine if there was significance to the relationship of the extent of use of culture in the classroom and academic achievement. There was no significance χ (6) = 9.83, p = .132 for reported academic achievement in mathematics in relation to the extent of culture use in the classroom; however, there was significance χ (6) = 18.325, p = .005 for the relationship between student reported academic achievement for reading and the extent of use of culture in the classroom.
Keywords: Academic Achievement; American Indian/ Alaskan Native; Culture; Indigenous; National Indian Education Survey